Impact of Covid-19 on Economy of Nepal - Pokhrel, Jagannath (Shaheed Smriti Journal, 2022)
This paper reviews the economic impact on various industries of Nepal due to Covid-19 pandemic which forced the Government of Nepal to enforce strict lockdown bringing the entire population and businesses to a halt. With worldwide travel coming to halt due to the pandemic, Nepal’s economy highly dependent on revenue from tourism took a massive hit. This paper looks at the consequences of pandemic on various businesses, household economy and nation’s financial outlook. This paper looks at GDP contribution by the tourism sector and how it is intertwined with several other businesses. This paper also analyzes the response by the Government of Nepal to handle the pandemic and how the country can recover from this severe downturn in the economy of almost all businesses in Nepal.